(3TQM ebOeI GHf GdMGLH aj GdfMhs - (3eLghds ((3eMeO Hf CMeO Hf fGUQ GdOjf GdMSjfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LdJ BdGDg Cf JMGW HYO hHYO abO WdH efi HYV ef GYJfi HUdGM MGd hCSYag HeG jSYg ebOQJi ef ebJQMGJ BeGdg JYdjb eGjLQi eLQi GdTQM Ydi ebOeI GHf GdMGLH ai GdfMh s
(3BNQgG (B:s
(3hdG Jdi gPg GdRjGOI gG GdScJ HNdGa RjGOI GdEacGQ dCf gPg EfeG JRGO EPG de jbUO Gdhba hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdfMhs